Interpretation of chronic pain clinical trial outcomes: IMMPACT recommended considerations. Issue 11 (November 2020) - Smith, Shannon M.; Dworkin, Robert H.; Turk, Dennis C.; McDermott, Michael P.; Eccleston, Christopher; Farrar, John T.; Rowbotham, Michael C.; Bhagwagar, Zubin; Burke, Laurie B.; Cowan, Penney; Ellenberg, Susan S.; Evans, Scott R.; et al.
Abstract : Abstract: Interpreting randomized clinical trials (RCTs) is crucial to making decisions regarding the use of analgesic treatments in clinical practice. In this article, we report on an Initiative on Methods, Measurement, and Pain Assessment in Clinical Trials (IMMPACT) consensus meeting organized by the Analgesic, Anesthetic, and Addiction Clinical Trial Translations, Innovations, Opportunities, and Networks, the purpose of which was to recommend approaches that facilitate interpretation of analgesic RCTs. We review issues to consider when drawing conclusions from RCTs, as well as common methods for reporting RCT results and the limitations of each method. These issues include the type of trial, study design, statistical analysis methods, magnitude of the estimated beneficial and harmful effects and associated precision, availability of alternative treatments and their benefit–risk profile, clinical importance of the change from baseline both within and between groups, presentation of the outcome data, and the limitations of the approaches used.